The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.17515/resm2022.348st1005
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effect and optimization of use of nano-TiO2 in cementitious composites

Abstract: There are some problems and weaknesses related to cement-based materials, such as their very low tensile strength, low chemical resistance and the huge contribution of cement production to industrial CO2 emissions. One possible method to reduce the impacts of such problems is the partial replacement of cement in cementitious materials with nano materials. This work provides a detailed review of incorporation of one of the most widely used nano materials, namely nano-titanium dioxide, and its effect on the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 107 publications
2
2
0
Order By: Relevance
“…The quantification indicator, i.e., the capillary water absorption coefficient, shows a significant decrease ranging from 37% to 81% compared to the capillary water absorption coefficient of the control sample. This observed trend is consistent with other literature references [33,36,37,41,57] and suggests a correlation with the evolution of the apparent density, indicating a densification of the material.…”
Section: Analysis Of the Physico-mechanical Characteristics Of Cement...supporting
confidence: 92%
See 3 more Smart Citations
“…The quantification indicator, i.e., the capillary water absorption coefficient, shows a significant decrease ranging from 37% to 81% compared to the capillary water absorption coefficient of the control sample. This observed trend is consistent with other literature references [33,36,37,41,57] and suggests a correlation with the evolution of the apparent density, indicating a densification of the material.…”
Section: Analysis Of the Physico-mechanical Characteristics Of Cement...supporting
confidence: 92%
“…Regarding the apparent density of the composites in the cured state at 28 days after casting, as shown in Figure 6a, it can be observed that it increases with the addition of NT, indicating a densification of the mass, in agreement with similar reports in the scientific literature [36,37,57]. The increase in this parameter is significant, reaching 7.4% for 2% NT and 6.7% for 3% NT compared to the NT-free sample.…”
Section: Analysis Of the Physico-mechanical Characteristics Of Cement...supporting
confidence: 88%
See 2 more Smart Citations